Perilaku cyberbullying sebagai masalah sosial remaja di era digital: analisis kajian literatur tentang perilaku, pengaruh lingkungan dan implikasinya bagi kesehatan mental. - Ulum, Ilsa Fikrotul (Maliki Interdisciplinary Journal, 2025)
Cyberbullying is a social problem that is increasingly prevalent among adolescents along with the development of digital technology and the increasing use of social media. This literature review aims to identify the forms of cyberbullying that occur, analyze the factors that influence it, and examine its impact on adolescent mental health. The results of the study indicate that cyberbullying can take the form of flaming, harassment, cyberstalking, denigration, masquerade, outing, and exclusion. Factors that influence the occurrence of cyberbullying include individual factors (impulsivity, emotions, self-control), family factors (supervision, parenting, support), peer factors (support and rejection), school factors (type, quality, and digital literacy), and intensive use of social media without balanced by good digital literacy. Cyberbullying has been shown to have a negative impact on adolescent mental health, including causing stress, anxiety, depression, low self-esteem, and even suicidal thoughts. Therefore, prevention and treatment efforts need to be carried out comprehensively, both within the family environment, school, and the digital community